From Learning to Memory: A Comparison Between Verbal and Non-verbal Skills in 22q11.2 Deletion Syndrome - Maeder, Johanna; Bostelmann, Mathilde; Schneider, Maude; Bortolin, Karin; Kliegel, Matthias; Eliez, Stephan (Frontiers in Psychiatry, 2021)
Background: Previous studies on possible memory deficits in 22q11DS often focused on quantifying the information memorized, whereas learning processes have been mostly overlooked. Furthermore, methodological differences in task design have made verbal and non-verbal comparison challenging and mixed results have been observed depending on chosen stimuli. Method: 135 participants (78 with 22q11DS) completed a multi-trial memory task modelled after the Rey Auditory Verbal Learning Task, comparing verbal as well as non-verbal learning as well as retention over time. Performance of 22q11DS participants were compared to controls and learning curves were analyzed. Results: In 22q11DS, slower acquisition of non-verbal material and higher rates of errors in both verbal and non-verbal tasks was observed. After 30 minutes, free recall performance, when corrected for initial learning rate, was similar between 22q11DS and controls. Conversely, recognition performance was overall weaker for 22q11DS in both modalities (verbal and non-verbal). Conclusion: This study examined how information is acquired, retained in memory over time and how different recall modalities (free recall vs. recognition) could yield different performances. Clinical implications of the findings are discussed.